Ministry of Local Government - Buganda Government
This file contains policy statements of the Ministry of Local Govern ment 1966, explanations of the estimates, 1966 and minutes of the meeti ngs held by the Ministry.
AR/BUG/1/4
Luganda and English
Shelf no. 1